Basic level English as foreign language teachers' experience about English medium instruction - Hari Prasad Tiwari (Northern Negros State College of Science and Technology (NONESCOST), 2023)
Medium of Instruction (MoI) used in teaching basic level students plays a significant role in their overall development. It is controversial whether students' native language or English is more effective for teaching students who study at the basic level. Nonetheless, many community schools are switching their MoI from Nepali, the country's official language, to English. The current descriptive phenomenological research aims to investigate basic level English as a Foreign Language (EFL) teachers' perspectives on English Medium Instruction (EMI) at the basic level. Nine basic level EFL teachers who have been teaching at different community schools in Nepalgunj Sub-Metropolitan City, Banke district, participated in the research. I used non-random judgmental sampling to select the sample. The data was collected using unstructured interview. The interviews were conducted in face-to-face mode and each of the interviews was audio recorded, transcribed, and then thematized. The outcomes of the research were presented and discussed utilizing descriptive and qualitative data analysis techniques. The results indicated that EMI has been mandated despite the fact that instructors lack the confidence to implement it in the classroom. Based on the results, it can be stated that EMI should be implemented with thorough planning, preparation, and consultation with teachers and other directly and indirectly engaged stakeholders in particular schools.